A representação da escravidão nos Contos de Machado de Assis - França Neto, João Irineu de (2008)
This work aims to study the theme of slavery in the tales written by Machado de Assis, having as corpus the analyses of the stories “Pai contra mãe”, “O caso da vara” and “Mariana”, which are meaningful narratives about enslavement, as they represent, by the realistic form, the oppression promoted by the enslaver society on the black people. In this case, we selected three analytical categories to organize our research: the speech of the narrator; the characterizing of the characters; and the representation of black men and women in social relations, established by the dominant classes in Brazil in the nineteenth century. The objectives of this research are: establishing an interchange between the aesthetical production and the social environment in the work of Machado de Assis; exploring the racial power relations in the nineteenth century which are represented in stories; analyzing the dialectical relationship between the formal resources of Machadian text and black stereotypes in the slave society of the nineteenth century. Amidst the types of studies in the scientific methodology, our research is characterized as bibliographical. The theoretical background presented in our research was composed by the following research areas: about the nature of literary language, we approached the contribution of the Russian formalist studies and dialectics in the composition process, proposed by Antonio Candido and Anatol Rosenfeld; about the historical role of the black and the slave system in Brazil, we had as main reference the studies from “Escravismo Colonial”, by Jacob Gorender. By the analyzes that we realized, we reached to the main conclusion that the issue of slavery of blacks in Brazil materializes, by the aesthetic and formal features of literary language and thereby representing some slaveholders contexts, by bias of irony, it leaves an ambivalence between the legitimation and criticism of the Brazilian slave system during the nineteenth century.